2011
DOI: 10.1007/s10658-011-9762-x
|View full text |Cite
|
Sign up to set email alerts
|

Fusarium species and DON contamination associated with head blight in winter wheat over a 7-year period (2003–2009) in Belgium

Abstract: The occurrence of Fusarium species in winter wheat in southern Belgium (Wallonia) and the deoxynivalenol content in 692 samples collected in commercial fields in the region's main cereal growing area were investigated. The main Fusarium species associated with head blight in wheat were identified at levels that varied from year to year. Interactions between fungal species causing head blight in wheat were detected, most of them positive. The years 2007 and 2008 were very conducive to the disease and there was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 31 publications
2
29
1
Order By: Relevance
“…In addition, long distance dispersal of viable F. graminearum spores is possible (MaldonadoRamirez et al 2005;Schmale et al 2012). We speculate whether the increased prevalence of FGSC observed in several European countries (Chandelier et al 2011;Jennings et al 2004;Stępień et al 2008;Waalwijk et al 2003) including the Nordic countries (Bernhoft et al 2010;Fredlund et al 2008;Nielsen et al 2011;YliMattila 2010) may have facilitated the introduction of the 15-DON genotypes into new areas like Norway and Denmark. As such, the prevalence of 15-ADON genotypes and associated mycotoxin levels in Norwegian cereals should be monitored.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…In addition, long distance dispersal of viable F. graminearum spores is possible (MaldonadoRamirez et al 2005;Schmale et al 2012). We speculate whether the increased prevalence of FGSC observed in several European countries (Chandelier et al 2011;Jennings et al 2004;Stępień et al 2008;Waalwijk et al 2003) including the Nordic countries (Bernhoft et al 2010;Fredlund et al 2008;Nielsen et al 2011;YliMattila 2010) may have facilitated the introduction of the 15-DON genotypes into new areas like Norway and Denmark. As such, the prevalence of 15-ADON genotypes and associated mycotoxin levels in Norwegian cereals should be monitored.…”
Section: Discussionmentioning
confidence: 84%
“…infection levels in cereal seeds, as well as the increased levels of trichothecene contamination in cereal grains, observed in Norway in recent years (Bernhoft et al 2013). During the same period, members of the Fusarium graminearum species complex (FGSC) have become more prevalent in several European countries (Chandelier et al 2011;Jennings et al 2004;Stępień et al 2008;Waalwijk et al 2003) including the Nordic countries (Bernhoft et al 2010;Fredlund et al 2008;Nielsen et al 2011;Yli-Mattila 2010), partly replacing other Fusarium species.…”
Section: Introductionmentioning
confidence: 99%
“…In studies conducted in Belgium in the years 2003-2009 a strong correlation was observed between the number of days with high relative humidity (above 80%) and mean annual DON content [31]. Twenty-one Fusarium spp.…”
Section: Resultsmentioning
confidence: 94%
“…Also, registered are products for biological protection. Plant protection against FHB, just as for other diseases, is not based solely on pesticide application but includes cultivar selection and a complex of preventive and agronomic strategies that can to a large extent prevent strong disease infection (Pereyra and Dill-Macky 2008;Chandelier et al 2011;Váňová et al 2011;Vogelgsang et al 2011;Landschoot et al 2012Landschoot et al , 2013. The purpose of comprehensive plant protection is to take into consideration all available methods that suppress the development of harmful organisms.…”
Section: Introductionmentioning
confidence: 99%
“…This group includes FHB, where some Fusarium species occur without apparent symptoms and the grain is nevertheless contaminated with mycotoxins. Although some recent papers have dealt with the effect of agronomic practices on FHB (Chandelier et al 2011;Vogelgsang et al 2011;Blandino et al 2012;Landschoot et al 2013), there remains a lack of knowledge about the effects of many factors and the interactions among them.…”
Section: Introductionmentioning
confidence: 99%